2021
DOI: 10.1021/acs.analchem.1c02555
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anti-Interference Strategy for a Self-Powered Sensor: Mediator-Free and Biospecific Photocathode Interface

Abstract: As a new electrochemical sensing concept, a self-powered sensor shows a good application prospect in the field of analysis. However, it is still a great challenge to improve the anti-interference capability of sensors through reasonable design. In this study, we investigated the difference between the single photoanode and photocathode self-powered sensor and combined the advantages of these two aspects to fabricate a mediator-free self-powered aptasensor based on the dual-photoelectrode system, which combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…† 44 In M-S plots, an n-type semiconductor gives a positive slope of the ramp, a p-type semiconductor gives a negative slope of the ramp, and the flatband potential (E fb ) of the n-type or p-type semiconductor can be obtained by intersecting the ramp-extension line of the M-S plot with the abscissa. 45,46 As shown in Fig. S4D-F, † we can conclude that In 2 O 3 , WO 3 and CdS QDs are all n-type semiconductors, and their E fb values are −0.42 V (vs. NHE), 0.85 V (vs. NHE) and −0.50 V (vs. NHE), respectively.…”
Section: Resultsmentioning
confidence: 66%
“…† 44 In M-S plots, an n-type semiconductor gives a positive slope of the ramp, a p-type semiconductor gives a negative slope of the ramp, and the flatband potential (E fb ) of the n-type or p-type semiconductor can be obtained by intersecting the ramp-extension line of the M-S plot with the abscissa. 45,46 As shown in Fig. S4D-F, † we can conclude that In 2 O 3 , WO 3 and CdS QDs are all n-type semiconductors, and their E fb values are −0.42 V (vs. NHE), 0.85 V (vs. NHE) and −0.50 V (vs. NHE), respectively.…”
Section: Resultsmentioning
confidence: 66%
“…The as‐constructed OECT‐PEC sensor inherits the advantages of the separate forms of signal from the excitation source (light illumination) and signal detection system (electric output) of the PEC sensor, resulting in a lower background signal and voltage‐free working electrode that effectively reduces possible interferences from electroactive substances. [ 9 ] Furthermore, it would also incorporate the advantages of the OECT, including excellent signal amplification and ease of miniaturization. [ 10 ] To date, only a few studies have reported the combination of a PEC and OECT.…”
Section: Introductionmentioning
confidence: 99%
“…A self-powered biosensing platform is an important implementation form for POCT due to its no additional power supply and easy miniaturization and has broad applications in clinical diagnosis, food analysis, environmental detection, and so forth. As one kind of self-powered biosensing platforms, several self-powered PEC sensors have been developed recently. For example, Yan et al reported a self-powered PEC aptasensor of PCB77 assay based on visible light-driven membraneless photocatalytic fuel cells .…”
Section: Introductionmentioning
confidence: 99%